Formation of the Information Economy: organizational and financial aspects - Nataliia Vdovenko; Jannet Deriy; Liudmyla Seliverstova; Petro Kurmaiev (International Journal of Supply Chain Management, 2019)
The relevance of the research topic is due to the fact that the modern process of globalization of the world economy has increased the importance of information in the process of social development. Information is a dominant factor in the competitiveness of national economies. The purpose of the study is to analyze the organizational and financial aspects of the formation of a global information economy. During the writing of the article, the following methods were used: generalization, comparative analysis and statistical analysis. The authors identify the main preconditions for the formation of the information economy: the technical and technological ability to implement projects; the readiness of the society for the changes that result from the functioning of the information economy. It is noted that information technologies are a catalyst for improving existing money market technologies, have created prerequisites for the distribution of FinTech 4.0, and the emergence of new inherently digital assets. The data of countries ranking in accordance with the degree of technical and technological ability to function within the framework of information economy is generalized. The main problems and obstacles of formation of elements of the information economy in Ukraine are established.